Cognitive Preoccupation with Breaking News and Compulsive Social Media Use: Relationships with Online Engagement and Motivations for Use. Issue 3 (27th May 2021) - Coduto, Kathryn D.; Anderson, Jennifer
ABSTRACT: The January 6, 2021, insurrection in the United States capitol can offer insight into how individuals engage with breaking news. The insurrection was a moment of national uncertainty; it was unclear who was storming the Capitol or why they were. A survey assessing cognitive preoccupation with breaking news online and compulsive social media use was developed and distributed within 48 hours of the insurrection. A sample of 380 college students revealed relationships between number of social media channels used, cognitive preoccupation with breaking news online, and compulsive social media use. Theoretical implications for the problematic internet use framework are discussed.